2013
DOI: 10.4187/respcare.01773
|View full text |Cite
|
Sign up to set email alerts
|

Conventional Weaning Parameters Do Not Predict Extubation Outcome in Intubated Subjects Requiring Prolonged Mechanical Ventilation

Abstract: BACKGROUND: Approaches to respiratory care of patients needing prolonged mechanical ventilation (PMV) might be varied. In this study we assessed the predictive value of usual variables for extubation outcome in PMV patients. METHODS: From 2005 to 2007, intubated patients who were admitted to the intermediate respiratory care unit, had been on mechanical ventilation for > 21 days at the time of admission, and underwent extubation after successful spontaneous breathing trials were included. Comparisons between s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
1
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 34 publications
2
31
1
6
Order By: Relevance
“…Finally, corroborating extensive evidence from the literature [8,15,40,45,] our study showed that EF is associated with worse global outcome. It is very likely that most of the observed associations in the patients in need for reintubation such as infectious complications, more frequent need for antibiotic treatment, longer sedation and ventilation times, and longer ICU-LOS may represent a chain of complications impacting that overall finding.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Finally, corroborating extensive evidence from the literature [8,15,40,45,] our study showed that EF is associated with worse global outcome. It is very likely that most of the observed associations in the patients in need for reintubation such as infectious complications, more frequent need for antibiotic treatment, longer sedation and ventilation times, and longer ICU-LOS may represent a chain of complications impacting that overall finding.…”
Section: Discussionsupporting
confidence: 90%
“…Coughing has been graded according to the clinically observed level of cough strength, usually qualitatively differentiating between 3 and 4 grades [39,40], by using a qualitative marker of cough efficiency like the ‘‘white card test,'' which evaluates the patients ability to cough secretions onto a card held in a short distance from the tube [41], or by adopting the technically more sophisticated quantitative measurement of cough peak flow with a pneumotachograph or a peak flow meter [32,35]. Irrespective of the method chosen, most studies have revealed that patients with a weak cough were at increased risk of EF [30,32,35,40,41,42]. More specifically, Thille et al [39] in their large prospective study suggested that reduced cough strength is associated with a 5-fold increased risk of reintubation, and that cough strength is even more important for extubation success than peripheral weakness.…”
Section: Discussionmentioning
confidence: 99%
“…An RCT including 181 patients has recently studied the effect of deflating the cuff on weaning and showed that deflating the tracheal cuff in tracheostomized patients shortened the weaning process compared with the inflated group (weaning time 8 days vs. 3 days, respectively; P < 0.01) and probably improved swallowing [46 && ]. In patients undergoing mechanical ventilation continuously for more than 21 days a multivariate logistic regression analysis showed that the only variable associated with extubation failure was ineffective cough and that weaning parameters were not helpful in predicting extubation outcome [47].…”
Section: Patients With Tracheostomy or Prolonged Mechanical Ventilationmentioning
confidence: 96%
“…Although not discussed here, there may be other populations considered to be HRFF for whom our recommendations may be applicable, such as patients with neuromuscular weakness or prolonged mechanical ventilator dependence. [18][19][20] …”
Section: Introductionmentioning
confidence: 99%